SUBTLE DIFFERENCES IN THE SEMANTIC RANGE, MEANING AND CONNOTATIONS OF WORDS RELATED TO HAPPINESS IN ENGLISH AND UZBEK (Ustozlar uchun, 2024)
Abstract: This article explores the subtle differences in the semantic range, meaning, and connotations of words related to happiness in English and Uzbek. It looks at how linguistic and cultural variations affect how these two languages interpret and express happiness. The essay attempts to reveal the subtleties and intricacies that lead to the distinct conceptualizations of happiness in each linguistic and cultural setting by examining a variety of words and their usage in both languages. The results illuminate the various perspectives and expressions of happiness, providing important new understandings of the relationship between language, culture, and feelings.